2002
DOI: 10.1074/jbc.m206355200
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Regulation of Phosphoinositide 3-Kinase in Retina through Light-induced Tyrosine Phosphorylation of the Insulin Receptor β-Subunit

Abstract: Recently, we have shown that phosphoinositide 3-kinase (PI3K) in bovine rod outer segment (ROS) is activated in vitro by tyrosine phosphorylation of the C-terminal tail of the insulin receptor (Rajala, R. V. S., and Anderson, R. E. (2001) Invest. Ophthal. Vis. Sci. 42, 3110 -3117). In this study, we have investigated the in vivo mechanism of PI3K activation in the rodent retina and report the novel finding that light stimulates tyrosine phosphorylation of the ␤-subunit of the insulin receptor (IR␤) in ROS memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(146 citation statements)
references
References 56 publications
6
138
2
Order By: Relevance
“…We showed previously that the important anti-apoptotic enzyme PI3K is regulated through light-activated IR in rod photoreceptor cells (2). In this study, we observed that light stress induced tyrosine phosphorylation of the IR in ROS membranes.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…We showed previously that the important anti-apoptotic enzyme PI3K is regulated through light-activated IR in rod photoreceptor cells (2). In this study, we observed that light stress induced tyrosine phosphorylation of the IR in ROS membranes.…”
Section: Discussionsupporting
confidence: 63%
“…IR activation has been shown to rescue retinal neurons from apoptosis through a phosphoinositide 3-kinase (PI3K) cascade (1). We previously reported that light induces tyrosine phosphorylation of the retinal IR and that this activation leads to the binding of PI3K to rod outer segment (ROS) membranes (2). More recently, we demonstrated that IR activation is mediated through the G-protein-coupled receptor rhodopsin (3).…”
Section: Insulin Receptor (Ir)mentioning
confidence: 99%
See 3 more Smart Citations